Internal landscapes : pain and trauma injury through the lens of subjective experience : an exegesis submitted in partial fulfillment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Sainsbury, Maria (Massey University, 2013)
My body resonates pain. Lying here, it’s like static on a radio infuriatingly monotonous and irritating in its regularity. Stabbing, burning, aching, it’s a constant vibration of stimulation. So wearying trying to stay on top of it. I’m waiting for the drugs to bring some relief so I can get on with the day. (This extract is taken from my diary before my third spinal surgery.) This thesis project was motivated by my subjective experience of constant pain over nearly a decade. Repeated spinal surgeries culminated in the implantation of rods and screws after a trauma accident. Through the process of research about pain I have recognised that its lack of an external referent makes it difficult to comprehend pain without visual trauma. The difficulty is that the pain experience is internal and not truly capable of being shared. Pain is multidimensional and includes many factors such as physical, mental, social and cultural environments that vary with individual circumstance. I haven’t presented my experience as a narrative but it does assist contextualising the works. I consider a multi discliplined approach to this project may help resonate this experience more articulately. I suggest that my subjective experience of pain manifests in an abstract form within my body. I seek to extrapolate traces of my interior experience by exploring a metaphorical and abstracted vocabulary of sound, sculpture and photography. I have referenced various theorists such as Elaine Scarry, Arne Vetleson and Amelia Jones. Similarly researching Artists from Modern and Contemporary fields such as Josek Sudek, Bob Flanagan, Hannah Wilke and Mona Hatoum. These theorists and artists are working or have worked with themes of pain, trauma and subjectivity. Further to this I have presented research papers at the Massey University Post Graduate Symposium 2012, Occulus - Canterbury University Post Graduate Symposium 2012, Art Association of Australia and New Zealand Annual Conference 2011 and the Zonta Organisation, Mana Chapter 2011. There is no definitive language that can accurately transcribe my subjective experience but I argue parts might be conveyed through a contemporary art project and those parts may ultimately be understood.
Keywords: Maria Sainsbury; Pain in art; Pain; Psychological aspects; Art practice; Subjectivity; Trauma injury; Metaphor; Photography; Sculpture; Sound; Multi disciplined